Analysis of stock price movement on Malaysian banking sector: using canslim method / Cyreenna Anak Jampi - Anak Jampi, Cyreenna (Faculty of Business and Management, 2018)
Bank is an important part for the financial systems stabilization. It plays a big role in the growth of our country's economy, it helps the now of money in the economy and secures the money supplies are set apart and given out towards growth and the development of financial. People especially investors have been encouraged by the banking activities toward investment which in turn is a part of economy growth. The theory of high-risk high return are the basic investing strategy that is used by most investors. An investing strategy named CANSLIM has been introduced in the 1950s. It was developed by William J. O'neil. An American stock research and Investor's Business Daily founder. CANSLIM is a growth stock investing strategy that combines both technical analysis and fundamental anal ysis. This strategy requires selecting stocks based upon seven criterions. CANSLIM stands for current earnings growth, annual earnings growth, new catalyst and new high, supply and demand, leader or laggard, institutional sponsorship, and market direction. Each of these stocks is analyzed with respect to these criteria to determine if it is likely to perform well. This techno-fundamental strategy helps pick quality stocks. This strategy focuses on companies that show acceleration in earnings because of innovation and suggests buying them before the stock price witnesses a major spike- The aim of this study is to identify the relationship between CANSLIM method towards stock price movement and Which factor affect the most towards stock price movement. The data are collected from year 2007 to 2010 on quarterly and annually basis. Stock prices of 10 selected banks; Maybank, CIMB Group Holdings, Public Bank, RHB Bank, Hong Leong Financial Group, AmBank Group, Hong Leong Bank Berhad, BIMB Holdings Berhad, Alliance Bank and Kenanga Investment Bank Berhad are used as dependent variable whereby current earnings growth, annual earnings growth, new products, new services, new management, new price highs, supply and demand. leader or laggard, institutional sponsorship, and market direction are used as the independent variables. The data will be analysed using panel data analysis and performance ranking model. The result from this study will share which stocks of the banks that have better performance in order to help investors in their investment strategy.